The Effectiveness of Immigration Regulations on Visa On Arrival 7 Days in Increasing Foreign Tourist Visits - Benardo, Adek Dio; Siadari, Lagat Parroha Patar; Nurkhotijah, Siti (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: This article analyzes the effectiveness of immigration regulations on the 7-day visa on arrival (VOA) in increasing international tourist arrivals.Purposes of the Research: The purpose of this article is to analyze the legal framework of the 7-day VOA policy from the perspectives of immigration and tourism, evaluate its implementation in increasing international tourist arrivals in Batam City, and identify obstacles while providing solutions to enhance the effectiveness of the policy.Methods of the Research: The research method employed combines normative juridical and empirical juridical approaches, with data collected through literature studies and field interviews at the Citra Tritunas Immigration Checkpoint in Batam City. It also applies a sociological (socio-legal) approach and theoretical analysis based on the perspectives of Lawrence M. Friedman and Soerjono Soekanto.Results Main Findings of the Research: The research findings indicate that although the 7-day VOA policy has been implemented administratively and supported by valid regulations, its execution remains suboptimal. The main obstacles arise from limited human resources, insufficient socialization, and low legal awareness among tourists. Therefore, it is necessary to strengthen the substance of the policy, enhance the capacity of immigration officials, integrate technology, and promote socialization involving tourism industry stakeholders. In this way, the policy is expected to be not only legally valid but also substantively effective in driving the growth of the national tourism sector.